Development of a Sensor-Based Telemonitoring System for Temperature, Dissolved Oxygen, pH, and TDS in Floating Net Cage Aquaculture - Humairoh Ratu Ayu; Bernitha Putri Liano; Jihan Puspita; Sri Wahyu Suciyati; Hilma Putri Fidyandini; Gurum Ahmad Pauzi; Amir Supriyanto (Journal of Energy, Material, and Instrumentation Technology, 2026)
Aquaculture using Floating Net Cage (FNC) systems in Lake Ranau, Lumbok Seminung District, West Lampung Regency, has expanded rapidly, with approximately 600 FNC units currently in operation. However, recurrent upwelling events frequently cause mass fish mortality and deterioration of water quality. Variations in temperature, dissolved oxygen (DO), pH, and total dissolved solids (TDS) significantly influence the overall water quality of the lake. To address these challenges, an Internet of Things (IoT)-based water quality telemonitoring system was developed for aquaculture applications, integrating temperature, DO, pH, and TDS sensors with an ESP32 microcontroller. Water quality data are transmitted in real time to the ThingsBoard platform, enabling continuous remote monitoring. Sensor performance evaluation demonstrated high measurement accuracy, with average accuracies of 98.87% for temperature, 98.37% for DO, 97.59% for pH, and 97.36% for TDS. These results indicate that the proposed telemonitoring system is reliable and effective for supporting water quality management in floating net cage aquaculture systems. Field testing conducted in the FNC system at Lake Ranau showed that the lake water quality was within safe limits, with temperature ranging from 25.32 °C to 29.15 °C, DO from 3.93 ppm to 7.48 ppm, pH values between 6.03 and 7.4, and TDS values below 1000 ppm.